2013
DOI: 10.3109/0167482x.2013.846904
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge about cervical cancer prevention and psychosocial barriers to screening among Mexican women

Abstract: The objectives of this study were to evaluate: Mexican women's knowledge about cervical cancer prevention; psychosocial barriers to screening; and the relation of both to cervical cancer screening behavior. Three hundred and eighty-four rural and urban women who had achieved a basic or higher educational level were surveyed. Almost 80% of the women had a Pap test but rural women were less likely to have done so. Although most women had received their most recent Pap within the last three years, only 29% had ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 21 publications
2
21
0
Order By: Relevance
“…A national cervical cancer screening program, part of the Official Mexican Standard, Norma Oficial Mexicana, began in 1974 and was relaunched between 1994 and 1998 [21]. The program recommends that screening begins aged 25 years or following the initiation of sexual activity; cervical smear tests are offered free of charge at public health institutions [22]. The guidelines indicate that women who experience two consecutive annual negative test results should decrease the frequency of screening to every 3 years [21,22].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A national cervical cancer screening program, part of the Official Mexican Standard, Norma Oficial Mexicana, began in 1974 and was relaunched between 1994 and 1998 [21]. The program recommends that screening begins aged 25 years or following the initiation of sexual activity; cervical smear tests are offered free of charge at public health institutions [22]. The guidelines indicate that women who experience two consecutive annual negative test results should decrease the frequency of screening to every 3 years [21,22].…”
Section: Resultsmentioning
confidence: 99%
“…The program recommends that screening begins aged 25 years or following the initiation of sexual activity; cervical smear tests are offered free of charge at public health institutions [22]. The guidelines indicate that women who experience two consecutive annual negative test results should decrease the frequency of screening to every 3 years [21,22]. In 1964, annual cytology screening was introduced in the former Soviet Union as part of routine cervical cancer screening; in 1976, the Ministry of Health established centralized cytology laboratories in all regions and republics of the former Soviet Union [23].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These beliefs have been associated with religious notions of shame or guilt around sexual matters which might result in negative health consequences [32]. Moreover, several studies have found that the Pap test is embarrassing for Mexican women [20, 33, 34]. The causes related to sexual behaviors were ranked as more severe in the results, signifying that these behavioral risk factors are stigmatized in this population.…”
Section: Discussionmentioning
confidence: 99%